Political Leadership in South Korea’s Developmental State: A Historical Revisit - Putri, Ratu Ayu Asih Kusuma (JAS (Journal of ASEAN Studies), 2018)
South Korea under President Park Chung Hee underwent rapid industrialization and experienced phenomenal economic growth making the country one of the Asian Tigers alongside Hong Kong, Taiwan, and Singapore. Had suffered by the long-standing Japanese colonialization, South Korea’s development strategies in its incipient economic venture, interestingly, postulate unforeseen similarities with those imposed by Japan primarily during the phenomenal industrial revolution of the Meiji government (1868-1912). Exponential modernization in South Korea was substantially forged by the implementation of ‘developmental state’ model. The term was initially coined by Johnson (1982) to explain the pacification of government policies – rather than market – to achieve successful economic rejuvenation of post-war Japan. In light to this historical paradox between South Korea and Japan, this article attempts to revisit the embarking point of South Korea’s rapid economic development beginning in the 1960s by drawing attention to the importance of leadership as one of the major components of the developmental state model. It concludes that Park Chung Hee’s strong Japanese linkage combined with his pretext for imposing ‘hard authoritarianism’ is particularly influential in determining South Korea’s pragmatic development trajectory.